Evaluasi Website Malasngoding dengan menggunakan Metode Usability Testing dan System Usability Scale (SUS) - Aditya Putra Pratama; Satrio Hadi Wijoyo; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Malasngoding is a learning media website that discusses programming languages ​​to build websites, applications and systems. The reason why using the malasngoding website as an evaluation topic, is because based on the similar.com website for the malasngoding website, it only has a total visitor of 315.11k, which turns out to be far from other similar websites and the visitor to the malasngoding website has decreased drastically from March to June. Initial research conducted on Filkom students, the general public, and students of SMK 5 majoring in RPL found several problems such as being unattractive and seeming messy, the appearance of the website on mobile tends to fill the screen, there is no function to contact the author, cannot subscribe to material via email, there is no table of contents to make it easier to see all the material, discussion positions that are not visible and some features cannot be used when accessing via mobile. This study uses the usability testing method and uses two questionnaires, namely the system usability scale and the General LMS evaluation. The test after repairing the malasngoding website and obtained results on the desktop device for the learnability aspect with a success rate of 96.2%, the efficiency aspect with time based efficiency 0.05 goals/sec, the error aspect with an error rate of 0.02, the memorability aspect with an average step of 53.3 and the satisfaction aspect an average score of 75.25. On mobile devices, the results of the learnability aspect with a success rate of 93.05%, the efficiency aspect with time based efficiency of 0.04 goals/sec, the error aspect with an error rate of 0.05, the memorability aspect with an average step of 67.7 and the satisfaction aspect with an average score of 74.55.